The Effect of Murottal Therapy on the Consciousness of Patients with Decrease of Consciousness: Case Report - Syahruramdhani; Rahmawati, Amirah (Universitas Muhammadiyah Yogyakarta, 2023)
unable to meet their basic needs, such as biological, psychological, sociological, and spiritual needs. Patients with decreased consciousness who are treated at PKU Muhammadiyah Yogyakarta Hospital are often given nursing care that focuses on illness and basic needs such as personal hygiene and nutrition. Nurses almost never try to provide complementary therapies or help meet the spiritual needs of patients with reduced consciousness. These complementary therapies include dhikr therapy and Al-Qur'an murottal therapy, which can help meet the spiritual needs of patients. Al-Qur’an murottal therapy is a recommended intervention because it is not only provides a therapeutic effect for the physical but also psychological and spiritual. Purpose – The purpose of this case study is to determine the effectiveness of Al-Qur'an therapy for patients who experience decreased consciousness. Methodology – The method used in this study is a case report. The author took one suitable patient and managed for approximately one week. The author assessed the patient as a whole, then measured the patient's level of consciousness and before and after the intervention. The intervention was carried out for six days. Each intervention is carried out for about three hours per day with the choice of surah based on the will of the family. Findings – The results showed that there’s no significant changes in the level of consciousness after being given murottal therapy for six days with a total duration of approximately three hours in a day, in a different section. Patient’s GCS changed from GCS E1V1M2 to E1V1M3. Implication – One of the studies showed that after the respondent was given Al-Qur'an stimulation treatment there was a change in the GCS score where the post test results after the 6th treatment were obtained from 10 respondents, nine of whom experienced a change in the level of consciousness